Analysis of diffusion strategies in northeast Brazil for new Cassava varieties with improved nutritional quality - González, C.; Pérez, S.; Cardozo, CE; Andrade, R.; Johnson, Nancy L. (Cambridge University Press, 2011)
Biofortified staple crops, amongst them cassava, are being developed to reduce problems of micronutrient malnutrition. In 2006 new cassava varieties with increased levels of provitamin A were released. For the purpose of enhancing adoption of the new cassava varieties, two strategies were used: (1) a participatory research approach and (2) public awareness raising activities. This paper attempts to evaluate the results of these two diffusion strategies. Within the first strategy, the factors found to enhance adoption rates were: awareness of the new varieties' advantages, public entities as the main information sources and involvement in participatory research. Within the second strategy, trends were found between adoption rates and producer characteristics including: ownership of land, middle-level income, advanced education level and use of information media, namely the Internet. In both strategies, a lack of seeds was one of the main factors limiting the adoption process.